2022
DOI: 10.3390/molecules27030923
|View full text |Cite
|
Sign up to set email alerts
|

A Green Method of Extracting and Recovering Flavonoids from Acanthopanax senticosus Using Deep Eutectic Solvents

Abstract: In recent years, green extraction of bioactive compounds from herbal medicines has generated widespread interest. Deep eutectic solvents (DES) have widely replaced traditional organic solvents in the extraction process. In this study, the efficiencies of eight DESs in extracting flavonoids from Acanthopanax senticosus (AS) were compared. Response surface methodology (RSM) was employed to optimize the independent variable including ultrasonic power, water content, solid-liquid ratio, extraction temperature, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…It may be attributed to the polyhydroxy nature of one of the components of the DES, which was glycerol. The importance of glycerol and glycerol‐based DESs as extracting solvents for bioactive compounds is demonstrated by a growing number of studies (Yazici & Ozmen, 2022; Zhang et al, 2022) and their function as extracting media has been mainly attributed to their polarity and ability to form hydrogen bonds with the target molecules such as polyphenols. The studies has suggested that DESs containing a polyhydroxy component may solubilize phenolics efficiently (Manousaki et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be attributed to the polyhydroxy nature of one of the components of the DES, which was glycerol. The importance of glycerol and glycerol‐based DESs as extracting solvents for bioactive compounds is demonstrated by a growing number of studies (Yazici & Ozmen, 2022; Zhang et al, 2022) and their function as extracting media has been mainly attributed to their polarity and ability to form hydrogen bonds with the target molecules such as polyphenols. The studies has suggested that DESs containing a polyhydroxy component may solubilize phenolics efficiently (Manousaki et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of glycerol and glycerol-based DESs as extracting solvents for bioactive compounds is demonstrated by a growing number of studies (Yazici & Ozmen, 2022;Zhang et al, 2022) and their function as extracting media has been mainly attributed to their polarity and ability to form hydrogen bonds with the target molecules such as polyphenols. The studies has suggested that…”
Section: Efficiency Of Extraction Parametersmentioning
confidence: 99%
“…Indeed, previous studies have used the above-mentioned DES to extract other active ingredients, but it is worth noting that almost all previous studies have synthesized DES and used them directly to extract active ingredients or for other purposes. For example, Tsvetov et al [24] used choline chloride and L-ascorbic acid to synthesize DES to extract bioactive components from chamaenerion angustifolium, Luo et al [25] used choline chloride and L-ascorbic acid to synthesize DES to extract secondary metabolites from eucommia ulmoides leaves, and Zhang et al [26] used glycerol and levulinic acid to synthesize DES extracting flavonoids from Acanthopanax senticosus, other functions include the synthesis of DES removal of copper corrosion products using choline chloride and L-ascorbic acid by Akiko Tsurumaki et al [27]. However, there are a few studies that have performed short-term storage of newly synthesized DES, for example, Andrew J Maneffa et al [28] used choline chloride and other compounds to synthesize DES.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an acceleration of extraction is more important for viscous solvents, i.e., NADES. Recently, this technique was successfully used for the extraction of polyphenols and flavonoids from various plant samples [17][18][19]. The mixtures of choline chloride and organic acids, such as malic and citric acid, are considered promising solvents for extracting the substances mentioned above [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%